1999
DOI: 10.1364/ol.24.000510
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Brillouin-loss spectrum of single-mode fibers by use of very short (<10-ns) pulses

Abstract: The characterization of the Brillouin-loss spectrum of single-mode fibers with very short (<10-ns) pulses has been studied. It was found that the Brillouin-loss signal intensity is linearly related to the duration of the pump pulse used to obtain the spectrum. In contrast with the uniform trend of the signal, three distinct behaviors were observed in the spectral linewidth. At long pulse durations the linewidth was constant at approximately 40 MHz. Pulse durations of the order of the phonon lifetime resulted i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
107
0
2

Year Published

2000
2000
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 158 publications
(115 citation statements)
references
References 4 publications
6
107
0
2
Order By: Relevance
“…7): The effect was first observed using this configuration [15]. The finite extinction ratio of the electro-optic modulator lets a continuous flow of pump light activate the acoustic wave, giving constant background amplification on the probe (dark topping).…”
Section: Brillouin Echo Distributed Sensing (Beds)mentioning
confidence: 99%
See 1 more Smart Citation
“…7): The effect was first observed using this configuration [15]. The finite extinction ratio of the electro-optic modulator lets a continuous flow of pump light activate the acoustic wave, giving constant background amplification on the probe (dark topping).…”
Section: Brillouin Echo Distributed Sensing (Beds)mentioning
confidence: 99%
“…The commonly accepted opinion that the spatial resolution of a pulse-based Brillouin sensor is limited to 1 m was seriously questioned when Bao et al observed an unexpected narrowing of the Brillouin gain spectrum down to its natural linewidth when pulses turned shorter than the acoustic lifetime (10 ns) [15]. This breakthrough opened the incredible perspective of performing high spatial resolution measurement while maintaining a sharp Brillouin resonance.…”
Section: Brillouin Echo Distributed Sensing (Beds)mentioning
confidence: 99%
“…Thanks to advanced and ingenious techniques the spatial resolution has been improved by at least 2 orders of magnitude from meter to centimeter range [1][2][3][4][5][6][7] , while recent efforts have been carried out to extend the distance range from some 30 km to 120 km and more by using remote amplification [8][9][10][11] or smart pump pulse coding [12][13][14][15][16] . Among the numerous publications in the field it remains difficult to fairly evaluate the real progresses that are reported without an objective metric based on a rationale.…”
Section: Introductionmentioning
confidence: 99%
“…The acoustic wave is not altered by this rapid change, but the response on the signal reflects the changes experienced by the pump. This has been first demonstrated by X. Bao et al in 1999 [4] and has been then widely improved and optimized [5][6][7], to reach a resolution of a few centimeters over a few kilometers.…”
Section: Description Of the Problema Ticmentioning
confidence: 96%